The effect of drill method on improving vocabulary mastery in children with intellectual disability - Annisa Mulyandari; Rizki Husadani; Sudarman Sudarman (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Children with Intellectual Disability experience limitations in cognitive and language abilities, including vocabulary mastery. The drill method, which emphasizes structured repetition, is considered effective for improving memory retention and vocabulary acquisition. Purpose: This study aims to determine the effect of the drill method on improving vocabulary mastery in children with Intellectual Disability in Klaten Regency. Method: The study used a quantitative approach with one group pretest-posttest design. The sample consisted of 15 children with Intellectual Disability aged 7-12 years selected through purposive sampling. The instrument used was the Expressive One-Word Picture Vocabulary Test (EOWPVT). The drill method intervention was conducted in 10 sessions, each lasting 45 minutes, using flashcard media. Results: The Wilcoxon Matched Pairs Test showed an Asymp. Sig. (2-tailed) value of 0,001 (p < 0.05), indicating a significant improvement in vocabulary mastery after the intervention. The mean pretest score of 60,60 increased to 72.33 in the posttest. Conclusion: The drill method has significant effect on improving vocabulary mastery in children with Intellectual Disability in Klaten Regency.